Synthesis of Novel Nanomagnetic Catalyst with Acetic Acid Tags: Application in the Synthesis of New Amidoalkyl Phenols under Solvent‐Free Condition. Issue 4 (25th January 2019) - Afsar, Javad; Khazaei, Ardeshir; Zarei, Mahmoud; Zolfigol, Mohammad Ali
Abstract: In this paper, [Fe3 O4 @SiO2 @(CH2 )3 ‐im‐CH2 CO2 H]Br was designed, synthesized and fully characterized by different techniques such as Fourier transform spectroscopy infrared (FT‐IR), scanning electron microscopy (SEM), energy‐dispersive X‐ray spectroscopy (EDX), elemental mapping, transmission electron microscopy (TEM), vibrating sample magnetometer (VSM) and thermal gravimetric analysis (TG). It was used as an efficient acidic nanomagnetic catalyst in the preparation of amidoalkyl phenols via multi‐component condensation of various amides (benzamide, acetamide and urea), phenolic compounds and aryl aldehydes or isatin under solvent‐free condition. High yield of products, easy work‐up and reusability of the catalyst can be mentioned as the advantages of described work. Abstract : [Fe3 O4 @SiO2 @(CH2 )3 ‐im‐CH2 CO2 H]Br was designed, synthesized and characterized by different techniques and used as an efficient nanomagnetic catalyst in the synthesis of amidoalkyl phenol derivatives via multi‐component condensation of phenolic compounds, various amides (benzamide, acetamide and urea) and aryl aldehydes or isatin under solvent‐free condition. Easy work‐up, short reaction times, high yields of products and recyclability of the catalyst are some advantages of this work.